Landslides and other earth movements damage detection at Mountain Village: A case at Garawastu - R., M. Nanda Fajar Arij; Satrio, Rio; Septyani, Yusan Nurul; Roprofil, M. Ridlo; Rifai, Andri Irfan (Indonesian Journal of Multidisciplinary Science, 2024)
Many countries have abundant natural resource but, on the other hand, also have the potential to experience land damage, which can result in natural catastrophes including landslides, floods, earthquakes, and volcanic eruptions. Potential land damage can impact the destruction of public facilities and hamper development; socio-economic conditions will stop when land damage occurs. This research aims to find and analyze possible land damage caused by land movement in the Cipari Hamlet area, Garawastu Village. Compiling a map of potential soil damage is the main focus of research because it can help understand the spatial distribution and extent of damage. Apart from using qualitative methods, field observations were also conducted to determine the coordinates of residents' houses affected by land damage by ground movement. Primary information and secondary information are the two categories of data. Original data comprises damage coordinates, UTM GEOMaps software, location maps, ArcGIS software, and documentation. Secondary data consists of maps and data, rainfall data from 2013 to 2022, and explanations of the results from ArcGIS software. Cipari Hamlet, Garawastu Village, experienced high rainfall, 3500-4000 mm. The slope in Cipari Hamlet ranges from 0-140, which is very flat to steep hills. Risks with a low level of damage get 17 points, risks with a medium level of damage are 9 points, and risks with a high level of damage get 9 points. Damage in the Cipari hamlet did not occur due to landslides because the index value for the Cipari hamlet was at a moderate point.